Arrhythmia prevention protocol during papaverine administration for invasive coronary functional assessment - Vassilev, Dobrin; Mileva, Niya; Stoev, Gavril; Pazardzhykly, Ilter; Panayotov, Panayot; Rigatelli, Gianluca; Gelev, Valery (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAccurate assessment of coronary physiology through invasive functional testing is critical for the effective management of chronic coronary syndromes. The induction of maximal and sustained coronary hyperemia is essential for obtaining reliable measurements of fractional flow reserve (FFR), coronary flow reserve (CFR), and the index of microcirculatory resistance (IMR). Intracoronary papaverine is a potent vasodilator for inducing hyperemia but has been associated with ventricular arrhythmias, limiting its clinical use.MethodsThis single-center prospective study investigates the feasibility and safety of a novel hyperemic protocol involving intravenous (i.v.) lidocaine administration followed by intracoronary papaverine in patients undergoing invasive coronary functional assessment. All patients underwent FFR, CFR, and IMR measurements after receiving an initial dose of 100 mg of i.v. lidocaine followed by papaverine (20 mg for the left coronary artery and 5–10 mg for the right coronary artery).ResultsA total of 389 patients were enrolled. Functionally significant stenosis (FFR ≤ 0.80) was identified in 36% of patients and microvascular dysfunction in 48%. Ventricular arrhythmias occurred in 1.5% of patients, including four episodes of ventricular fibrillation and two of ventricular tachycardia; all resolved with prompt defibrillation and without hemodynamic compromise.ConclusionThese findings suggest that pre-treatment with lidocaine may enhance the safety of papaverine-induced hyperemia during invasive coronary testing.